Determining Near Point of Convergence: Exploring a Component of the Vestibular/Ocular Motor Screen Comparing Varied Target Sizes - John D Heick; Curt Bay (International Journal of Sports Physical Therapy)
# Background Near point of convergence (NPC), a component of the Vestibular Ocular Motor Screening (VOMS) assessment, may be helpful in diagnosing concussion. The VOMS uses a standardized approach to measure NPC; however, methods of screening for NPC are not standardized.